Evaluation of role of heart rate variability with holter monitoring in chronic kidney disease - Avula, Naveen Reddy; Dighe, Tushar; Sajgure, Atul; Bale, Charan; Wakhare, Pavan (International Journal of Research in Medical Sciences, 2020)
Background: Chronic kidney disease is prevalent disease even in absence of diabetes and hypertension in 12% adults over 65 yrs of age. Autonomic imbalance is not studied in detail which could be a risk factor for chronic kidney disease. Methods: This Study was observational study in a tertiary care Hospital in pune, india and was conducted for a period of 1 year with sample size of 52. All subjects were known cases of chronic kidney disease from stage III to VD. All individuals of age >18yrs and eGFR ≤60ml/min/1.73m2 according to CKD- EPI equation were included in the study and who were not giving consent were excluded. 24 hrs Holter monitoring was done in stages from ckd stages III to V, for ckd stage VD on both Hemodialysis day and Non hemodialysis. Analysis was done using SPSS version 20 (IBM SPSS Statistics Inc., Chicago, Illinois, USA) Windows software program. The paired t test, analysis of variance (ANOVA) and Chi-square test were used. Level of significance was set at p≤0.05. Results: In this study when Heart rate variability (HRV) parameters were compared in different stages of ckd from stage III to VD (on Hemodialysis day) SDNN, SDNN Index were found to be statistically significant and on non Hemodialysis day SDNN Index was found to be statistically significant. In each subgroup of ckd stage V when diabetic subjects were compared with non-diabetic subjects, HRV parameters like ratio of P/S which was found to be low and significant in ckd stage V diabetic subjects. Conclusions: Chronic kidney disease itself can affect the HRV parameters. Causal relationship between HRV and chronic kidney diseases can be vice versa and further needs larger and prospective studies.